Macro Variable Effect Analysis and NonPerforming Financing (NPF) Against the Return on Asset (ROA) Islamic Banks in Indonesia Year 2008- 2017 - Karisma, Dwi Pratika; Qolbi, Fikri ‘Ainul; Rosyadi, Imron (Journal of Islamic Economic Laws, 2020)
Islamic Banks is a business entity that raises and distributes funds from the community and for the community. The study was conducted to analyze the macro variables and NPF (NonPerforming Finance) to ROA (Return on Assets) to determine the relationship between short-term and long-term between variables. The analysis model used is the Engle Granger ECM Stage Two test that uses secondary data from the serial data (time series). The results of this study indicate that NPF simultaneously, GDP, and interest rates affect the ROA. Partially GDP positive and significant effects in the long term and short term, NPF positive and significant effect in the long term, interest rate, and no significant positive effect on ROA.